Framework in remodelling new Malaysian Standard Method of Measurements (SMMs) / Anis Rosniza Nizam Akbar - Nizam Akbar, Anis Rosniza (2018)
Standard Method of Measurement (SMM) is a standard document localized to fit the local custom and practice, thus serving as standardized measurements fundamental to producing a good Bill of Quantities. However, previous studies have revealed issues of key players not being underpinned by an SMM deemed necessary for a review, which subsequently invalidating its status in becoming an acceptable model and resulting in the generation of low-standard BQ. Despite these issues being justified by previous researchers, the lack of efforts towards displaying a preferred resolution have rendered them daunting still and remaining as an academic and industry-wide concern. Therefore, this research aims to propose a framework in remodelling the current Malaysian SMMs for Construction Works into a model that is more acceptable. It has subsequently outlined five specific objectives, which include: investigating current practices implemented by the industry in measuring and preparing BQs for construction works; examining issues related to Malaysian SMMs; analysing suitable characteristics of Malaysian SMMs model; developing a framework used in remodelling New Malaysian SMMs; and finally, assessing the suitability and validity of the developed framework. A triangulation approach has been adopted to obtain wide-ranging information regarding similar issues, whereby the strengths of various approaches may be implemented to overcome the insufficiency of others. Data collection processes have been completed through techniques like literature review, documents analysis, questionnaire survey, interviews and focus group discussions. This particular work has disclosed the importance and urgency of improving the construction industry, achievable by remodelling the current Malaysian SMMs model using a proposed framework to be applied. Comprised o f a set of phases and steps to be followed and performed during the process, the framework has also been incorporated with major issues and elements identified during the course of the research. It has been designed with the aim of assisting committee members or decision makers with a guideline or checklist regarding variables necessary in remodelling New Malaysian SMMs model that is more acceptable by making it simple, clear, practical and comprehensive.